Crowd And Acoustical Modelling In Digital Cultural Heritage - Lim, Chen Kim (2014)

(untitled)
The broad term of heritage refers to the study of human activity in the past and its cultural narratives and to virtualize heritage means to actualize the heritage content digitally. Istilah warisan secara meluas merujuk kepada kajian kegiatan manusia pada masa lampau dan pengkisahan budayanya dan memayakan warisan bermaksud merealisasikan kandungan warisan secara digital.